Persepsi Apoteker terhadap Hambatan dalam Pelayanan Kefarmasian Penyakit Asma Di Apotek: Pharmacist Perception of Barriers in Pharmaceutical Services for Asthma Disease in Pharmacies - Amelia Lorensia; Ananda Yudiarso; Nurul Safina (Jurnal Sains dan Kesehatan, 2020)
One to improve the services of asthma pharmacy at pharmacies is to know the barrier (pharmacy) pharmacists in the pharmacy services of asthma itself. However, there is still a pharmacist barrier in providing pharmaceutical services of asthma namely Perceived barrier on self-efficacy pharmacist, Perceived barrier on counseling, Perceived barrier on knowledge of the patient, and Perceived barrier on the role of pharmacist. The aim of this research is to know deksriptif and to explore perception of pharmacist to barrier of pharmacy service of pharmacy at pharmacy in Surabaya. This research is a research of mixed methods with sequential explanatory research design. Instruments in this study using questionnaires and interviews. Sampling with non-random sampling method with purposive sampling technique, then the data will be processed descriptively. The sample of research were 53 pharmacists representing 1 pharmacist, 41 pharmacists willing to fill out questionnaires but not willing to interview and 12 pharmacists willing to fill out questionnaires and interviews. Barrier data based on Kritikos et al. (2010), was examined with the most commonly used approach, HBM (Health Believe Model), which is a model of individual health trust in determining the attitude of doing or not doing health behavior. The results of the study show that pharmacists still have barriers in pharmacy services from 4 dimensions, including: self-efficacy, pharmaceutical counseling, perceived knowledge of patients, and the role of pharmacists..